,

m = ( m0, m1, m2... mk- 1

). (1.62)

:

m(x)= m0 + m1 × x + m2 × x2 +...+mk- 1 × xk-1. (1.63)

m(x) xn-k:

xn-k × m(x)= m0 × xn-k + m1 × xn-k+1 +...+mk- 1 × xn-1

, (1.64)

n-1

.

,

xn-k × m(x) = q(x) × g(x) + r(x) , (1.65)

q(x) r(x) xn-k × m(x) g(x).

g(x) (n-k), r(x) (n-k-1) , r(x)

r(x)= r0 + r1 × x + r2 × x2 +...+ rn- k- 1 × xn-k-1 . (1.66)

GF(2) :

r(x) + xn-k × m(x) = q(x)× g(x) , (1.67)

, r(x)+xn-k × m(x)

g(x) n-1 . , r(x)+xn-k

× m(x) - , m(x).

,

r(x)+m(x)× xn-k

=r0 +r1 x +r2 x2 ..+rn- k-1 xn-k-1 + m0 xn-k

+ m1 × xn-k+1 + ..+ mk-1 xn-1,

U

=

( r0, r1 ... rn- k-1 ,

m0, m1 ... mk-1),

 

, m, (n-k) .